Ethics in qualitative research - Miller, Tina 1957- (London SAGE, 2012)
This fresh, confident Second Edition expands its focus on the theoretical and practical aspects of doing qualitative research in light of new ethical dilemmas facing researchers today. In a climate of significant social and technological change, researchers must respond to increased ethical regulation and scrutiny of research. New sources, types of data and modes of accessing participants are all challenging and reconfiguring traditional ideas of the research relationship. This engaging textbook explores key ethical dilemmas - including research boundaries, informed consent, participation, rapport and analysis - within the context of a rapidly changing research environment. The book effectively covers the ethical issues related to the data collection process, helping readers to address the ethical considerations relevant to their research.